Effectiveness Of Ct-Scan Parameters For Nasopharyngeal Examination In Clinical Nasopharyngeal Carcinoma Toward Anatomical Information At The Radiology Department Of Rst Dr. Reksodiwiryo Padang - Livia Ade Nansih; Nerifa Dewilza; Cicillia Artitin; Salsa Gitta Nabila (PT. Hafasy Dwi Nawasena, 2026)
Nasopharyngeal carcinoma is one of the malignant tumors of the head and neck that requires accurate imaging evaluation, with CT scanning being one of the primary modalities. This study aims to determine the effectiveness of CT-scan parameters for evaluating anatomical information in patients with clinically diagnosed nasopharyngeal carcinoma at the Radiology Department of RST Dr. Reksodiwiryo Padang. The research employed observational methods and in-depth interviews with two radiographers and one radiologist, along with a review of patient CT images. Data were collected regarding patient preparation, examination technique, and the conformity of parameters with theoretical standards. The examination was performed with the patient in a supine head-first position, using a scan area from the MAE to the thoracic vertebrae III, slice thickness of 5 mm, window width of 350, and window level of 40. The results showed that although these parameters differ from theoretical recommendations—which suggest a 2.5-mm slice thickness and a more superior scan range—they were still able to visualize essential anatomical structures, including thickening of the nasopharyngeal roof, intracerebral extension, maxillary sinus opacity, parapharyngeal space, oropharynx, paranasal sinuses, orbital cavity, parotid glands, and mastoid air cells. The diagnostic information was considered sufficient to establish the diagnosis of nasopharyngeal carcinoma; however, the radiologist recommended expanding the superior scan range to evaluate the temporal lobe and intracranial involvement when necessary. In conclusion, the CT-scan parameters used at RST Dr. Reksodiwiryo Padang are effective for assessing nasopharyngeal carcinoma, although further optimization remains advisable